Comparison of daily vs. weekly single-dose ferrous sulphate treatment in female junior high students with iron deficiency anemia - Dedy Afandi, Sri Mulatsih, Madarina Julia (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Complianc~ of daily treatment of iron deficiency anemia in children is still low. The compliance will be increased if the iron supplementation is given weekly. Previous study showed that there was no significant difference in the increase in hemoglobin level between daily and weekly treatment in prepubertal children. Objective: To study the difference in the increase in hemoglobin and serum ferritin levels between daily and weekly sirigle-dose treatment of ferrous sulphate in female junior high school students with iron deficiency anemia after menarche. Methods: This was a quasi-experimental study recruiting 179 and 174 anemic female students in the weekly and daily group, respectively. They receive weekly or daily single-dose of ferrous sulphate capsules. Hemoglobin levels were measured before and after the 12 weeks treatment, while serum ferritin levels were measured before and after in a subset of the study subjects. Result: Mean:t SD levels of hemoglobin before and after iron supplementation were 11.18:1: 0.51 and 12.79:t0.63 g/dl (p=0.001) in the weekly group, and 11.17:1:0.61 and 12.68:1:0.57 g/dl (p=0.001) in the daily group. Mean:l: SD levels of ferritin before and after iron supplementation were 6.95:1: 1.85 and 41.5:1:33.93 ng/ml (p=0.001) in the weekly group, and 6.61 :1:2.17 and 40.7:1:22.73 ng/ml (p=0.001) in the daily group. The prevalence of anemia after supplementation is similar in both groups, i.e. 6.7% in the weekly group and 8.0% in the daily group (p = 0.631. There were no significance difference in the occurrence of side effects of diarrhea and nausea in both groups (p>0.05). Conclusion: This study concluded that daily vs. weekly ferrous sulphate supplementation did not result in significantly different level of both hemoglobin and serum ferritin after treatment. The difference in the occurrence of side effects was also not statistically significant. Key words: anemia iron deficiency - hemoglobin level - serum ferritin level - ferrous sulphate